Non-Heart-Beating Cadaver Procurement and the Work of Ethics Committees - Spielman, Bethany (Cambridge quarterly of healthcare ethics, 1997)
Recent ethics literature suggests that issues involved in non-heart-beating (NHB) organ procurement are both highly charged and rather urgent. Some fear that NHB is a public relations disaster waiting to happen or that it will create a backlash against organ donation. The purpose of the study described below was to assess ethics committees' current level of involvement in and readiness for addressing the difficult issues that NHB organ retrieval raises—either proactively through policy development or concurrently through ethics consultation.